Relationship between ground reaction force and stability level of the lower extremity in young active adults - Sato, K.; Poczwardowski, A.; Butcher, M. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
The purpose of this study was to identify the relationship between GRF and the stability level of the lower extremity to define the risk of running-related injuries. 13 participants were divided to two groups (previous running injury; no previous running injury) and performed a Single-leg Excursion Test (SET), and ran across a force plate to measure GRFs. Results showed a moderate negative correlation, (r(10) = -0.620, p < 0.05). The injury group had higher GRF and lower SET scores as compared to the no injury group, Runners that can reduce the GRF and improve their stability level in the lower extremity by performing proper strength and stability training may reduce the risk of injuries from running activities.